ANALISIS KESESUAIAN TRANSPORTASI BUS RAPID TRANSIT (BRT) DI KOTA TASIKMALAYA: BELAJAR DARI MODEL TRANSJAKARTA - Muhamad Kahar Dwitama; Gheitsa Nur Fadhila, Riziq Afgiansyah, Mochammad Fakhri, Akbar Muhammad Zamzam, Yani Sri Astuti (Jurnal Ekonomi dan Bisnis, 2024)
Transportation is a crucial element in urban development, influencing the economy and regional growth. Tasikmalaya city, with its unique characteristics, seeks effective transportation alternatives. This research analyzes the suitability of the online-based Bus Rapid Transit (BRT) concept with the characteristics of Tasikmalaya city, using TransJakarta as a learning model. A qualitative method is used with a holistic and comparative analysis approach. The results indicate that although BRT has advantages in serving passengers, the geographic conditions, infrastructure, and scale of Tasikmalaya city still do not support the effective implementation of BRT. Various challenges such as lower traffic density and infrastructure limitations must be overcome before the successful implementation of BRT can be achieved. This research is expected to provide insights for the development of effective and sustainable transportation strategies in Tasikmalaya city, as well as insights for other cities in Indonesia facing similar challenges.